2004
DOI: 10.3201/eid1002.030534
|View full text |Cite
|
Sign up to set email alerts
|

SARS Transmission among Hospital Workers in Hong Kong

Abstract: Despite infection control measures, breakthrough transmission of severe acute respiratory syndrome (SARS) occurred for many hospital workers in Hong Kong. We conducted a case-control study of 72 hospital workers with SARS and 144 matched controls. Inconsistent use of goggles, gowns, gloves, and caps was associated with a higher risk for SARS infection (unadjusted odds ratio 2.42 to 20.54, p < 0.05). The likelihood of SARS infection was strongly associated with the amount of personal protection equipment percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
211
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(225 citation statements)
references
References 2 publications
5
211
2
7
Order By: Relevance
“…The key learning points from the SARS epidemics [26,27], particularly those concerning infection control, are summarised in table 1.…”
Section: Lessons From the Sars Epidemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key learning points from the SARS epidemics [26,27], particularly those concerning infection control, are summarised in table 1.…”
Section: Lessons From the Sars Epidemicsmentioning
confidence: 99%
“…In addition to staff absence due to personal infection, quarantine and caring duties, high stress levels may impact Data taken from [26,27].…”
Section: Human Workforce Plans and Regulationsmentioning
confidence: 99%
“…[4][5][6][7] Contamination of the skin and clothing of health care personnel contributes to transmission of pathogens and places personnel at risk for infection with potentially fatal pathogens, such as Ebola virus, severe acute respiratory syndrome, and Middle East respiratory syndrome coronaviruses. 1,[8][9][10][11] Moreover, personnel frequently acquire norovirus infections during health care facility outbreaks and are at risk of acquiring CDI if they receive antibiotics. [12][13][14] The risk of inadvertent contamination of skin and clothing despite use of PPE may be particularly high during removal of contaminated equipment.…”
Section: Invited Commentarymentioning
confidence: 99%
“…We understand that the purpose of a surgical mask is the prevention of surgical wound contamination and subsequent patient infection, not personal protection. However, these guidelines and test standards did not stop the widespread practices of health care workers and domestic users in the community to wear surgical and other facemasks as a key personal protective device during the SARS outbreak in Hong Kong, Taiwan, and Toronto [Seto et al, 2003;Lau et al, 2004;Loeb et al, 2004;Chen et al, 2005]. Seto et al [2003] reported that surgical facemasks did provide significant protection for health care workers taking care of SARS patients.…”
Section: Reply To the Comments On ''In Vivo Protectivementioning
confidence: 99%